Relation between Festivals and Economic Activities in Nepal - Dhakal, Chandra Prasad (Nepal Journal of Multidisciplinary Research, 2022)
Festivals are the main events of people to purchase new clothes, household goods and necessary gadgets like mobile phone, television, computer, furniture etc. In the study it analyzes the relation between cultural and religious as well as other festivals that play vital role to enhance the economic activities in the nation. Main objectives so this study is to analyze how festivals play role enhance economic activities in Nepal and why such tradition has still been sustained in Nepal and what are the relationship between festivals activities and economic activities. To fulfill the objectives, the study follows mixed method and analyzed the both qualitative and qualitative data collected from only secondary sources. Conclusion and findings are made on the basis of data analysis and presentation.